Global Effect of Interleukin-10 on the Transcriptional Profile Induced by Neisseria meningitidis in Human Monocytes - Gopinathan, Unni (American Society for Microbiology, 2012)
In meningococcal septic shock, the dominant inducer of inflammation is lipopolysaccharide (LPS) in the outer membrane of Neisseria meningitidis, while interleukin-10 (IL-10) is the principal anti-inflammatory cytokine. We have used microarrays and Ingenuity Pathway Analysis to study the global effects of IL-10 on gene expression induced by N. meningitidis, after exposure of human monocytes (n = 5) for 3 h to N. meningitidis (10(6) cells/ml), recombinant human IL-10 (rhIL-10) (25 ng/ml), and N. meningitidis combined with rhIL-10. N. meningitidis and IL-10 differentially expressed 3,579 and 648 genes, respectively. IL-10 downregulated 125 genes which were upregulated by N. meningitidis, including NLRP3, the key molecule of the NLRP3 inflammasome. IL-10 also upregulated 270 genes which were downregulated by N. meningitidis, including members of the leukocyte immunuglobulin-like receptor (LIR) family. Fifty-three genes revealed a synergistically increased expression when N. meningitidis and IL-10 were combined. AIM2 (the principal molecule of the AIM2 inflammasome) was among these genes (fold change [FC], 18.3 versus 7.4 and 9.4 after stimulation by N. meningitidis and IL-10, respectively). We detected reduced concentrations (92% to 40%) of six cytokines (IL-1b, IL-6, IL-8, tumor necrosis factor alpha [TNF-α], macrophage inflammatory protein alpha [MIP-α], MIP-β) in the presence of IL-10, compared with concentrations with stimulation by N. meningitidis alone. Our data analysis of the effects of IL-10 on gene expression induced by N. meningitidis suggests that high plasma levels of IL-10 in meningococcal septic shock plasma may have a profound effect on a variety of functions and cellular processes in human monocytes, including cell-to-cell signaling, cellular movement, cellular development, antigen presentation, and cell death.